Anticipating future threats: evidence for association, but not interaction, of childhood adversity and identity development with threat anticipation in adolescence - Samaey, Celine; Lecei, Aleksandra; Achterhof, Robin; Hagemann, Noëmi; Hermans, Karlijn S. F. M.; Hiekkaranta, Anu P.; Kirtley, Olivia J.; Reininghaus, Ulrich; Boets, Bart; Myin-Germeys, Inez; van Winkel, Ruud (Early intervention in psychiatry, 2024)
AIM: Childhood adversity may result in a negative expectation of future interactions with others, also referred to as 'threat anticipation'. It may also negatively impact on identity development, which subsequently may influence how individuals deal with their environment. Here, we examine the hypotheses that (1) identity synthesis is associated with reduced anticipation of threat, whereas the opposite would be true for identity confusion, and (2) that identity confusion exacerbates the association between childhood adversity and threat anticipation. - METHODS: One thousand nine hundred and thirteen adolescents from the general population (mean age = 13.8 years, SD = 1.86, range = 11-20) completed self-report questionnaires assessing exposure to childhood adversity, identity development and threat anticipation. - RESULTS AND DISCUSSION: Identity development was significantly associated with threat anticipation in the expected direction: identity synthesis was associated with reduced anticipation of threat (β = -.0013, p < .001), whereas identity confusion was association with increased threat anticipation (β = .0017, p < .001). Furthermore, childhood adversity was positively associated with threat anticipation (β = .0018, p < .001). However, no evidence for an interaction effect of identity on the association between childhood adversity and threat anticipation was found, suggesting childhood adversity and identity development have an independent rather than synergistic effect on threat anticipation. - CONCLUSION: The current study illustrates the importance of exposure to childhood adversity and identity development for threat anticipation in adolescence. Further research is needed to clarify how both factors influence each other within a developmental framework.
Online ahead of print
Gesehen am 29.08.2024